New Aspects in Molecular and Cellular Mechanisms of Human Carcinogenesis 2016
DOI: 10.5772/61151
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cancer Stem Cells in Head and Neck Squamous Cell Carcinoma and Its Clinical Implications

Abstract: Worldwide, more than , new cases of head and neck squamous cell carcinoma HNSCC are estimated to occur annually, making it the sixth most common human malignancy. Since their discovery in , cancer stem cells CSCs in HNSCC have garnered increased interest secondary to their properties of tumorigenicity, differenti-ation, proliferation, and self-renewal. CSCs are intrinsically more resistant to tradi-tional treatments such as radiation and chemotherapy, contributing to potential metastasis and recurrence of HNSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Cancer stem cells are recognized and characterized by the following features, uncontrollable proliferation, self-renewal, massive differentiation, immune evasion, and treatment resistance. Cancer stem cells have been implicated in various cancers following treatment failure [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Cancer stem cells are recognized and characterized by the following features, uncontrollable proliferation, self-renewal, massive differentiation, immune evasion, and treatment resistance. Cancer stem cells have been implicated in various cancers following treatment failure [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Despite ongoing advances in treatment regimes, the prognosis for HNSCCs has improved only marginally over the past 30 years, with the 5-year survival rate ranging from 10% -50% depending on a number of factors including the clinical stage of the tumor at the time of diagnosis (Karimnejad et al 2016;Yan et al 2013). Standard therapy for HNSCCs includes a combination of surgery, chemotherapy and radiotherapy, which is determined by the histological variety, grade and clinical staging of the tumor (Zhu et al 2015).…”
Section: )mentioning
confidence: 99%
“…Standard therapy for HNSCCs includes a combination of surgery, chemotherapy and radiotherapy, which is determined by the histological variety, grade and clinical staging of the tumor (Zhu et al 2015). However, irrespective of the treatment regime, patients exhibit relatively high rates of local recurrence as well as regional cervical lymph node and distant tumor metastases, which contribute to significant morbidity and mortality (Karimnejad et al 2016;Zhu et al 2015). Recurrent tumor and metastatic deposits are frequently resistant to the original treatment modalities utilized (Karimnejad et al 2016;Zhu et al 2015).…”
Section: )mentioning
confidence: 99%
“…Furthermore, it has been reported that the tumor recurs in the primer locus, and resistance to treatment occurs in 50% of patient treatments . Recent studies have shown that the factor decreasing the efficacy of all these treatments is the cancer stem cell, which has a progenitor‐like feature in the tumor mass and a subpopulation of cancer cells . Head and neck cancer stem cells (HNCSC) are in a niche localized around blood vessel.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recent studies have shown that the factor decreasing the efficacy of all these treatments is the cancer stem cell, which has a progenitor-like feature in the tumor mass and a subpopulation of cancer cells. 12 Head and neck cancer stem cells (HNCSC) are in a niche localized around blood vessel. The cancer stem cell maintains its self-renewal and survival in the niche with secretion factors and nutrients and oxygen supplied by endothelial cell.…”
mentioning
confidence: 99%